Тестування вбудованих інформаційно комунікаційних систем: порівняння ручного та автоматизованого підходів - Чушкіна, В. А. (ХНУРЕ, 2025)
This article analyzes testing methods for embedded information and communication systems, comparing manual and automated approaches. The research aims to determine the effectiveness of each method, considering their advantages, limitations, and practical applications. The main focus is on identifying optimal testing strategies to ensure the reliability and stability of embedded systems. Experimental results demonstrate the efficiency of automation in regression testing and the necessity of manual testing in exploratory scenarios.
Keywords: тестування вбудованих систем; testing method for communication systems